PENGARUH MODEL PICTURE AND PICTURE TERHADAP HASIL BELAJAR SISWA MATERI HAK DAN KEWAJIBAN KELAS III UPTD SDN 29 MENDO BARAT - Pratiwi, Ines; Yurdayanti; Wahyuningsih, Eka (STKIP Subang, 2026)
The issue underlying this study is the low learning outcomes of students in the topic of rights and obligations, which is caused by the limited variation in teaching models, leading to students being less engaged and easily bored during learning activities. The purpose of this study is to evaluate the impact of the Picture and Picture model on the learning outcomes of third-grade students at UPTD SDN 29 Mendo Barat. This study adopts a quantitative approach using the Pre-Experimental Design method with a One Group Pretest-Posttest Design. The sample in this study consists of all third-grade students at UPTD SDN 29 Mendo Barat. The data collection process used essay questions, and the data evaluation method employed the Shapiro-Wilk Normality Test for normality testing and the Wilcoxon Signed-Rank Test for hypothesis testing. The results of the study show a significant effect on the Pretest and Posttest outcomes. The normality test calculation for the Pretest was 0.053 > 0.05, and for the Posttest, it was 0.004 < 0.05, indicating that the data was not normally distributed. Therefore, hypothesis testing was conducted using the Wilcoxon Signed-Rank Test. The result of the hypothesis test was 0.000 < 0.05, meaning H_a was accepted and H_o was rejected. Thus, it can be concluded that the Picture and Picture model has an impact on the learning outcomes of third-grade students on the topic of rights and obligations at UPTD SDN 29 Mendo Barat.